Lymphomatoid Granulomatosis of Central Nervous System and Lung Driven by Epstein Barr Virus Proliferation: Successful Treatment with Rituximab - Ruben Fernandez; Esther Gonzalez; Almudena Fernandez; Ana Pilar Gonzalez; Juan Manuel Sancho; Francisco Dominguez; Carmen Fernandez (Mediterranean Journal of Hematology and Infectious Diseases)
Lymphomatoid granulomatosis (LYG) is a very rare Epstein-Barr virus (EBV) associated B-cell lymphoproliferative disorder. We report the case of a 41-year-old man who presented with fever and respiratory symptoms. Computed tomography showed multiple nodules in both lung fields. Polymerase chain reaction (PCR) analysis of the bronchoalveolar lavage was positive for EBV and biopsy of lung node yielded a diagnosis of LYG, grade III. Shortly after initiation of treatment with chemotherapy, neurologic deterioration appeared. Radiologic findings revealed hydrocephalus and PCR analysis of the cerebrospinal fluid (CSF) was positive for EBV. Treatment with intravenous rituximab led to rapid reduction of EBV load in CSF, along with radiological and clinical improvement. After completion of treatment with immunochemotherapy, an autologous stem cell transplantation was performed. Patient stays in remission one year after diagnosis.